Effects of Photoperiod on the Development of Forensically Important Blow Fly Chrysomya rufifacies (Diptera: Calliphoridae). Issue 5 (18th April 2020) - Bauer, Amely M; Bauer, Alexandra; Tomberlin, Jeffery K
Abstract: Estimation of the time of colonization (TOC) is often based on laboratory studies that document arthropod development. Precise data for forensically important species, such as blow flies (Diptera: Calliphoridae), are essential for accuracy in the estimate of TOC. Calliphorid development is a quantitative trait and thus depends on a host of variables. In calliphorids, studies showed photoperiod can play a role in development. However, there has been little research to date on the effects of photoperiod, and available data indicate the impact is species-specific. In this study, the effects of photoperiod on the development of Chrysomya rufifacies (Macquart), were examined. Chrysomya rufifacies is a fly of great medical and legal importance and is often encountered on vertebrate remains in temperate and tropic regions throughout the world, including North and Central America, Asia, and Australia. Larvae were reared under light regimes of 12, 16, and 24 h of light at 28.5 ± 0.0°C, 86.2 ± 0.3 RH. Minimum development time for each stage did not differ significantly for the applied photoperiods, nor were there significant differences in total minimum postembryonic development time. Photoperiod did not significantly affect larval size or growth rate. The data suggest that light durations investigated in this study do not influence the development of C. rufifacies . This indicates that photoperiod may not be a concern for forensic entomologists in Texas, United States, or other areas with similar conditions when estimating the TOC for this species. Validation efforts are encouraged to verify this conclusion.